Religious Moderation as Paradigm for Development of Islamic Education at Pondok Pesantren Al-Ikhlas Addary DDI Takkalasi, Barru - Muhammad Suryadi R; Hannani Hannani; Muzakkir Muzakkir; Muhammad Saleh; Buhaerah Buhaerah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study explores the implementation of religious moderation as a paradigm for developing Islamic education at Pondok Pesantren Al-Ikhlas Addary DDI Takkalasi, Barru Regency. Using a qualitative phenomenological approach, the research involved kyai, teachers, and students through in-depth interviews, observations, and document analysis. The findings reveal that values of moderation—such as balance (tawazun), tolerance (tasamuh), justice (ta‘adul), and proportionality (i‘tidal)—are systematically integrated into the curriculum, institutional culture, and character formation. The pesantren applies a reflective-dialogical learning model in which teachers guide students to interpret Islamic teachings contextually within social realities. The kyai’s moral example functions as a “hidden curriculum” that strengthens students’ moral awareness and social responsibility. Moreover, the pesantren’s inclusive culture fosters solidarity and empathy among students of diverse backgrounds. Religious moderation has thus evolved from a normative concept into an educational paradigm guiding curriculum design, institutional management, and character education. This paradigm reflects a holistic and integrative model of Islamic education that harmonizes spiritual, intellectual, and social dimensions. It not only preserves Islamic tradition but also responds to contemporary challenges of pluralism, nationalism, and modernization. The study concludes that religious moderation serves as a constructive paradigm for developing a reflective, humanistic, and civilized generation in Islamic boarding schools.